The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1111/j.1751-0813.1998.tb12362.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for the preservation of koala (Phascolarctos cinereus) semen

Abstract: By controlling the growth of bacteria in extended koala semen, penicillin G and gentamicin are likely to lengthen the period by which spermatozoa can be stored at 16 degrees C and reduce the possibility of disease transmission during artificial insemination procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
(9 reference statements)
0
9
0
1
Order By: Relevance
“…Studies describing the use of antimicrobials in the preservation of semen from wild animals ( Table 1) are even more scarce than in companion animals. The combination of penicillin (1000 IU/mL) and gentamicin (100 μg/mL) was effective at preserving koala semen (Phascolarctos cinereus) at 16 °C for 24 h as it prevented bacterial growth without interfering on the sperm motility (Johnston et al, 1998). Additionally, the addition of gentamicin (70 μg / mL) (Santos et al, 2019a) and a combination of penicillin (2000 IU/mL and 1000 IU/mL)-streptomycin (2 mg/mL and 1 mg/mL) (Santos et al, 2019b) to the semen of collared peccaries (Pecari tajacu) allowed the control of bacterial growth in the samples and did not present toxic effects on the quality of the chilled semen maintained up to 36 h. Due to the differential action of antimicrobial substances in the distinct species, various studies have been conducted in order to stablish appropriate antimicrobial concentrations in the diluent.…”
Section: Use Of Antibacterial Substances In Semen Extendersmentioning
confidence: 99%
“…Studies describing the use of antimicrobials in the preservation of semen from wild animals ( Table 1) are even more scarce than in companion animals. The combination of penicillin (1000 IU/mL) and gentamicin (100 μg/mL) was effective at preserving koala semen (Phascolarctos cinereus) at 16 °C for 24 h as it prevented bacterial growth without interfering on the sperm motility (Johnston et al, 1998). Additionally, the addition of gentamicin (70 μg / mL) (Santos et al, 2019a) and a combination of penicillin (2000 IU/mL and 1000 IU/mL)-streptomycin (2 mg/mL and 1 mg/mL) (Santos et al, 2019b) to the semen of collared peccaries (Pecari tajacu) allowed the control of bacterial growth in the samples and did not present toxic effects on the quality of the chilled semen maintained up to 36 h. Due to the differential action of antimicrobial substances in the distinct species, various studies have been conducted in order to stablish appropriate antimicrobial concentrations in the diluent.…”
Section: Use Of Antibacterial Substances In Semen Extendersmentioning
confidence: 99%
“…In an attempt to improve our basic knowledge and thereby facilitate the management of wild and captive Koala populations, a series of studies, critical to the development of an AT programme, was carried out (Johnston, 1999). Three key areas were investigated: (1) semen collection (Johnston et al, , 1997a and preservation (Johnston et al, 1992(Johnston et al, , 1993(Johnston et al, , 1998(Johnston et al, , 2000a, (2) detection of oestrus and the timing of ovulation (Johnston et al, 2000b) and (3) anatomy of the 9 reproductive tract to determine the most appropriate site for the deposition of semen (Johnston, 1999).…”
Section: Development Of Artificial Insemination Techniquesmentioning
confidence: 99%
“…To maintain some degree of long-term sperm preservation in the koala, it was found that their semen can be extended with the addition of Tris-citrate Glucose (TCG) when held at 5 °C (Johnston et al, 2000c), with the addition of antibiotics (penicillin G and gentamicin) to control the growth of bacteria (Johnston et al, 1998). Finally, more advanced methods to determine sperm integrity and fertilisation capacity have been developed, so that assessment of sperm quality is no longer based on motility alone.…”
Section: Assisted Breeding Technologies In Koala Conservationmentioning
confidence: 99%
“…All semen was collected by means of electro-ejaculation (EJ) while the koala was under a surgical plane of anaesthesia, using procedures previously described in detail by Johnston et al (2000a) All koala ejaculates were immediately diluted 1:1 with room temperature TCG buffer after collection; the TCG was composed of 3.0 g Tris base (Sigma Aldrich, Australia), 1.7 g citric acid (Sigma Aldrich, Australia) and 1.25 g glucose (Sigma Aldrich, Australia), made up to 100 mL with Milli-Q Ultrapure water (Millipore Australia Pty Ltd., North Ryde, NSW, Australia) and adjusted to a pH of 7.4 (Johnston et al, 2006). Unless otherwise stated, the TCG also contained penicillin G and gentamicin (Sigma Aldrich) at 1000 IU mL -1 and 100 µg mL -1 , respectively (Johnston et al, 1998).…”
Section: Koala Samples and Semen Collection And Preparationmentioning
confidence: 99%